RESPONSIBILITIES OF BANK BJB COORPORATE SOCIAL RESPONSIBILITY (CSR) RECIPIENTS IN THE BORDER AREA OF WEST JAVA - Haspada , Deny (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2022)
This research is intended to find out how responsible answer from beneficiary of social funds company as well as to test the influence of profitability and company size of the Bank as a Regional Government - Owned Enterprise (BUMD). Current developments require companies to increase their attention to the social environment. The existence of large companies such as banks in Indonesia is expected to bring positive change and development to the lives of the surrounding community especially the border with giver social funding assistance . Companies are not only faced with responsibilities in obtaining profit alone, companies must also pay attention to social and environmental responsibilities. If the community thinks that a company does not pay attention to its social and environmental aspects and does not feel a direct contribution and even feels a negative impact from the operation of a company, this condition will create a negative stigma among the community. One form of accountability is by disclosing social responsibility which is often called Corporate Social Responsibility (CSR). Social responsibility is an approach that integrates social care within the company and in interactions with stakeholders based on the principles of volunteerism and partnership. The implementation of CSR in Indonesia is regulated in Law no. 40 of 2007 concerning Limited Liability Companies, which explains how companies are responsible for the social environment. The company is responsible for social and environmental problems arising from the implementation of company activities. The method used in This research is a normative juridical approach, namely legal research conducted by examining literature or secondary data as a basis for research by conducting a search of regulations and literature related to the problem under study. This research use descriptive-analytical research , and empirical that is through two stages research namely library research and field research. Library research is the main research stage, while field research is only a support for library data . The mandatory outputs resulting from this research activity include : an article entitled “ Recipient Responsibilities Bank BJB's Corporate Social Responsibility (CSR) in the Border Region West Java ”, expected could published in accredited national journals with a minimum of Sinta 3 ( three ).